The impact of assisted reproductive technologies versus natural conception on neonatal intensive care unit admission: A retrospective cohort analysis - Huajuan Chen; Hui Shao; Lei Xu; Xiujuan Wang (PLoS ONE, 2025)
Background The rapid advancement of assisted reproductive technology (ART), coupled with the increasing prevalence of advanced maternal age, has led to a global rise in ART-conceived neonates. Whether these reproductive methods affect neonatal health outcomes, particularly regarding the risk of neonatal intensive care unit (NICU) admission, has become a critical concern in perinatal medicine. Objective This study aimed to compare the risk of NICU admission between neonates conceived naturally and those conceived through ART in a large cohort population, with important implications for optimizing perinatal care and improving neonatal outcomes. Methods A retrospective study was conducted to analyze the baseline data of 3,867 singleton mothers and their neonates, who were either pregnant through ART or spontaneous conception, at a tertiary maternity hospital in Zhejiang Province from 2022 to 2024. Propensity score matching (PSM) was employed to match seven potential confounders that might affect the outcomes. Logistic regression analyses (univariate and multivariate, pre- and post-PSM) assessed the association between gestation mode and NICU admission risk, with additional multivariable-adjusted models for deeper investigation.Additionally, subgroup analyses were conducted pre- and post-PSM to explore how the mode of gestation impacts the risk of neonatal NICU admission in different population subsets. Finally, PSM was applied to five maternal factors (age, BMI, gestational weeks, gravidity,parity, and pregnancycomplications). Differences in neonatal characteristics, such as gestational weeks, birth weight, delivery method, and delivery-related hemorrhage, were compared across different gestational modes pre- and post-PSM using box scatter plots.We also performed mediation analysis to assess the potential mediating effects of confounding factors, including the mode of delivery and gestational weeks. Results Among 3,867 births, 265 neonates were admitted to the NICU. Restricted cubic spline logistic regression analyses demonstrated that ART-conceived neonates had a lower risk of NICU admission compared to naturally conceived neonates, both before and after PSM.This may be attributed to enhanced prenatal monitoring and selective embryo transfer in ART pregnancies, which could mitigate adverse perinatal outcomes. Subgroup analyses before PSM identified an interaction between cesarean section and ART, which was not observed after PSM.Overall, the results of the subgroup analyses suggest that neonates born through ART have a lower risk of NICU admission across various population subgroups. Box scatter plots showed that ART-conceived neonates had shorter gestational weeks, lower birth weights, higher cesarean section rates, and greater intrapartum hemorrhage (all P < 0.05), with no significant difference in sex distribution (P > 0.05).Additionally, the mediation analysis quantified the effect sizes mediated by delivery mode and gestational age. Conclusion ART-conceived neonates have a reduced risk of NICU admission compared to naturally conceived neonates,potentially due to optimized prenatal care and embryo selection offsetting the risks associated with shorter gestation and lower birth weight.However, the elevated rates of cesarean delivery and intrapartum hemorrhage in ART pregnancies require ongoing clinical attention to improve maternal and neonatal outcomes. These findings suggest that while ART may confer neonatal benefits, it carries important maternal risks that warrant consideration in clinical decision-making.